STRATEGI KEPALA MADRASAH DALAM MENGEMBANGKAN KOMPETENSI INTERPRENURE BERBASIS AL-QUR’AN - Suci Hidayati; Marno Marno; M. Fahim Tharaba (university Of islam, 2023)
Madrasah principals have a major influence on the marketing and existence of their educational institutions. entrepreneurial competence must be possessed by every madrasah principal which is a form of creativity and effort of a leader in creating an institutional environment that has a business spirit. This study aims to determine the strategies and their implementation carried out by madrasah heads in developing entrepreneur competencies in educational institutions based on the Qur'an. The objects in this study were MTs Almaarif 02 Singosari and MTs. Wahid Hasyim 02 Dau, Malang Regency. The approach and method used in this research is qualitative research in the form of field research (Field Research). The results of the study show that the strategy developed by the head of the madrasa and his staff has had a positive impact on the advancement of Al-Qur'an-based institutions and learning. In the implications of developing entrepreneurial competence, the two institutions apply two ways, namely collaboration and accommodation strategies with superior programs, namely (1) Field Experience Practice Program (PPL) to Al-Qur'an Education Parks for grade 9 students who are trained with Al-Qur'an learning methods 'a Tilawati and (2) the Tahfidz Weekend Program (weekend) for SD/MI students in the madrasa environment who want to memorize the Qur'an at an affordable cost. This study concludes that the two programs that develop Al-Qur'an-based entrepreneurial competence can attract the interest of the community around the institution so that the two institutions continue to exist and are increasingly advanced in Al-Qur'an education. In the future, there is an opportunity for institutions to invite people who want their children to be proficient, memorize and at the same time teach the Al-Qur'an to enroll in madrasah.